STRUKTUR KOMUNITAS MAKROINVERTEBRATA SEBAGAI BIOINDIKATOR UNTUK MENENTUKAN STATUS KUALITAS AIR DI SUNGAI CANDIPARI, SIDOARJO - Dita Afrilia; Yusrianti Yusrianti; Abdul Hakim; Amrullah Amrullah (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
Rivers are ecosystems that play an important role in the lives of living things around them. The river is not balanced if there are disturbances such as activities around it. Candipari River is one of the polluted rivers which is influenced by the activities in the vicinity. This study aims to determine the quality of river water using the macroinvertebrate community structure (diversity index, dominance index, and BMWP-ASPT). This research uses a biomonitoring method with macroinvertebrate bioindicators, and the retrieval technique uses kicking and jabbing techniques. Measurement of water quality can be seen based on the biological components contained in the water. These biological components are found in water such as macroinvertebrates. These macroinvertebrates can be used as bioindicators, by knowing the role of macroinvertebrates as bioindicators to determine water quality. Analysis of macroinvertebrate data can be identified and calculated by determining the index value. The results of the water quality research based on the BMWP-ASPT method are that at station 1 is a river in the Very Polluted category with a value of 3.57, at stations 2 and 3 a river in the Moderately Polluted category with a value of 4.